Elaborating principles of idiom-formation in the avant-garde literary discourse: a case study of Russian Cubo-Futurism (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
The paper sets out to explore the avant-garde literary discourse from the point of view of its idiomatic constituent. In particular, it studies avant-garde manifestoes written by the representatives of Cubo- Futurism, in which radical aesthetic renewal and the need for the reformation in the sphere of literature are proclaimed. As very expressive and complex rhetorical performances, manifestoes contain various kinds of idiomatic phrases that can be considered both vivid representations of a particular (avant-garde) approach to the language and prescriptions for certain ways of the language use. Special attention is paid to the elaboration of the methodology aimed to identify avant-garde idioms proper in the avant-garde literary discourse. The results obtained show that the manifestoes under consideration are, in essence, the first “trials” in the field of (poetic) language reformation and language experimentation and the sources of the idiomatics (idioms / idiomatic expressions) that can be termed “experimental”.
Keywords: avant-garde discourse, manifesto, avant-garde idiomatics, experimentation